Recent Advances in Water-Tolerance in Frustrated Lewis Pair Chemistry - Fasano, Valerio; Ingleson, Michael J. (Synthesis, 2018)
A water-tolerant frustrated Lewis pair (FLP) combines a sterically encumbered Lewis acid and Lewis base that in synergy are able to activate small molecules even in the presence of water. The main challenge introduced by water comes from its reversible coordination to the Lewis acid which causes a marked increase in the Brønsted acidity of water. Indeed, the oxophilic Lewis acids typically used in FLP chemistry form water adducts whose acidity can be comparable to that of strong Brønsted acids such as HCl, thus they can protonate the Lewis base component of the FLP. Irreversible proton transfer quenches the reactivity of both the Lewis acid and the Lewis base, precluding small molecule activation. This short review discusses the efforts to overcome water-intolerance in FLP systems, a topic that in less than five years has seen significant progress.1 Introduction2 Water-Tolerance (or Alcohol-Tolerance) in Carbonyl Reductions3 Water-Tolerance with Stronger Bases4 Water-Tolerant Non-Boron-Based Lewis Acids in FLP Chemistry5 Conclusions
Keywords: water-tolerance; frustrated Lewis pairs; Lewis acid; Lewis base; reduction